Sustainable Tourism Development in Indonesia: Challenges and Solutions - Madya, Faizal; Ambia Arma, Nur; Ratih wulandari, Florentina (Iapa Proceedings Conference, 2025)
Tourism is a strategic sector in Indonesia’s national development, contributing significantly to economic growth, job creation, and the promotion of cultural identity. However, uncontrolled tourism activities have the potential to lead to environmental degradation, social inequality, the loss of local cultural identity, economic disparities, excessive concentration of tourism in certain destinations, and inconsistencies with the principles of sustainable development. This paper aims to analyze sustainable tourism strategies in Indonesia, emphasizing the integration of economic, social, cultural, and environmental aspects. The approach used in this paper is a literature review, policy analysis, and governance strategy analysis combined with an environmentally conscious tourism development framework. The analysis shows that sustainable tourism development must balance economic, social, and environmental dimensions in accordance with the principles of sustainable development (Brundtland Report). Strengthening multi-level governance, implementing the principle of Free, Prior, and Informed Consent (FPIC), managing carrying capacity, and empowering local economies are key strategies for creating a sustainable tourism system. Furthermore, the implementation of Community-Based Tourism (CBT) and the diversification of tourist destinations outside of core areas are considered capable of expanding economic benefits and reducing ecological pressures. This article emphasizes that the success of Indonesian tourism development depends on collaboration between stakeholders, green fiscal policies, and a commitment to cultural and environmental protection.